Health care cost increases - Meyer, Jack A.; American Enterprise Institute (Washington : American Enterprise Institute for Public Policy Research, 1979)
This book deals with the rising cost of health and other related problems. It further examines the problem associated with the consumer expenditures for health care.
Includes bibliographical references.
mf 21/01/2019
Loans
Keywords: Medical care, Cost of; Medical care; Medical policy